2003
DOI: 10.1073/pnas.1431443100
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome sequence of the marine planctomycete Pirellula sp. strain 1

Abstract: Pirellula sp. strain 1 (''Rhodopirellula baltica'') is a marine representative of the globally distributed and environmentally important bacterial order Planctomycetales. Here we report the complete genome sequence of a member of this independent phylum. With 7.145 megabases, Pirellula sp. strain 1 has the largest circular bacterial genome sequenced so far. The presence of all genes required for heterolactic acid fermentation, key genes for the interconversion of C1 compounds, and 110 sulfatases were unexpecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
383
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 446 publications
(406 citation statements)
references
References 48 publications
16
383
0
4
Order By: Relevance
“…Expression level prediction based on codon usage optimization was calculated for each gene in the R. baltica genome according to the method described by Karlin et al [43]. Highly expressed reference genes including ribosomal proteins, translation factors and chaperonins were extracted from the published annotation of R. baltica [26].…”
Section: Signal Peptides and Gene Expression Levels Predictionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Expression level prediction based on codon usage optimization was calculated for each gene in the R. baltica genome according to the method described by Karlin et al [43]. Highly expressed reference genes including ribosomal proteins, translation factors and chaperonins were extracted from the published annotation of R. baltica [26].…”
Section: Signal Peptides and Gene Expression Levels Predictionsmentioning
confidence: 99%
“…The category "metabolism" was further divided into eight sub-categories ( Table 2). The sub-category "sulfatases" was used, since the presence of 110 sulfatase-encoding genes was one of the major unexpected findings from the annotation of the R. baltica genome [26], 10 of which were identified on the gel. The pattern of identified proteins displayed in Fig.…”
Section: Proteins With Functional Assignmentmentioning
confidence: 99%
See 1 more Smart Citation
“…11 MBL2 polymorphisms have been shown to be associated with increased risk of infection 12,13 and to alter the phenotypic expression of autoimmune diseases. 14,15 MBLs are proved to be common in the entire evolutionary scale, from bacteria, 16 to plants, to humans, while structural homologs of MBL2 have been found in several mammals (including humans, cow, 17 pig, 18 rabbit, 19 mouse 20 and rat 21 ), in chickens 22 and also in fishes. 23 A possible homolog has even been found in the tunicate, Styela plicata, 24 but MBL2, structurally speaking, is a typical vertebrate protein.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the genome sequences of the different P. marinus strains led to the identification of genes, which play a role in determining the relative fitness of the ecotypes in response to key environmental variables [11]. Glöckner et al [13] reported the complete genome sequence of Pirellula sp. strain 1 ('Rhodopirellula baltica SH1'), a marine representative of the globally distributed and environmentally important bacterial order Planctomycetales.…”
Section: Individual Organismsmentioning
confidence: 99%